2015
DOI: 10.1016/j.str.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Damage-Inducible 1 Protein (Ddi1) Contains an Uncharacteristic Ubiquitin-like Domain that Binds Ubiquitin

Abstract: SUMMARY Ddi1 belongs to a family of shuttle proteins targeting polyubiquitinated substrates for proteasomal degradation. Unlike the other proteasomal shuttles, Rad23 and Dsk2, Ddi1 remains an enigma: its function is not fully understood and structural properties are poorly characterized. We determined the structure and binding properties of the ubiquitin-like (UBL) and ubiquitin-associated (UBA) domains of Ddi1 from Saccharomyces cerevisiae. We found that, while Ddi1UBA forms a characteristic UBA:ubiquitin com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 64 publications
4
95
3
Order By: Relevance
“…In contrast, our data do not support the proteasome shuttling mechanism, as deletion of UBL, UBA or both did not impair the ability of the protein to rescue hydroxyurea sensitivity. Our findings also contrast with the so-called alternative proteasomal shuttle hypothesis proposed by Nowicka and coworkers (Nowicka et al 2015a), which suggests that the first Ddi1 UBL domain binds polyubiquitinated substrate and the other UBL targets the proteasome. The hydroxyurea hypersensitivity phenotype of the double-mutated Δddi1, Δwss1 yeast strain can be partially complemented even with a minimal construct comprising the double helical bundle followed by the RVP domain (Ddi1 146-322).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, our data do not support the proteasome shuttling mechanism, as deletion of UBL, UBA or both did not impair the ability of the protein to rescue hydroxyurea sensitivity. Our findings also contrast with the so-called alternative proteasomal shuttle hypothesis proposed by Nowicka and coworkers (Nowicka et al 2015a), which suggests that the first Ddi1 UBL domain binds polyubiquitinated substrate and the other UBL targets the proteasome. The hydroxyurea hypersensitivity phenotype of the double-mutated Δddi1, Δwss1 yeast strain can be partially complemented even with a minimal construct comprising the double helical bundle followed by the RVP domain (Ddi1 146-322).…”
Section: Discussioncontrasting
confidence: 99%
“…3.3. The multi-helical bundle preceding the RVP domain is essential for Ddi1's role in the DNA replication stress response NMR and X-ray scattering experiments have shown that yeast Ddi1 is a multi-domain protein composed of multiple structured domains separated by flexible linkers Nowicka et al 2015b). To test whether Ddi1 works in replication stress reversal as a whole protein or if only some of its domains are involved, we created plasmids encoding truncated variants of the protein lacking one particular domain (summarized in Fig.…”
Section: Hydroxyurea Hypersensitivity Can Be Rescued By Overexpressiomentioning
confidence: 99%
“…An unusual protease that can bind ubiquitin was recently described by Lehrbach and Ruvkun, who found that processing of the Nrf1 homolog in C. elegans requires Ddi1 [6], and by Murata and colleagues, who showed that its human homolog, Ddi2, is required for Nrf1 processing (personal communication). Ddi1/2 contain an aspartyl protease domain resembling that in retroviruses [8], but they also are UbL/UbA proteins that bind to both ubiquitinated proteins and proteasomes [9, 10]. We recently confirmed that HAP1 cells lacking Ddi2 cannot process Nrf1 (Fig S2).…”
mentioning
confidence: 73%
“…Rpn1 associates with UBL domains found in auxiliary proteins Rad23/hHR23, Dsk2/hPLIC/Ubiquilin, Ddi1, and Ubp6/USP14, all of which also contain a domain with high affinity for polyUb (Aufderheide et al, 2015; Elsasser et al, 2002; Kim et al, 2004; Nowicka et al, 2015; Peth et al, 2009; Peth et al, 2013a; Rosenzweig et al, 2012). The paralog subunit, Rpn2, has been shown to form tight interactions with the polyUb receptor Rpn13/ADRM1, and with the proteasome-associated DUB, UCH37/UCH-L5 (Aufderheide et al, 2015; Bashore et al, 2015; Hamazaki et al, 2006; He et al, 2012; Sakata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%